2019
DOI: 10.17221/311/2018-cjfs
|View full text |Cite
|
Sign up to set email alerts
|

Yogurt ice cream sweetened with sucrose, stevia and honey: Some quality and thermal properties

Abstract: This study investigated the effects of some sweeteners (sucrose, honey and stevia) on the quality and thermal properties of plain (P) and cocoa (C) yogurt ice cream. For this purpose, six different yogurt ice cream samples were prepared with sucrose (control: AP, AC), with honey (BP, BC) and with stevia (CP, CC). The highest values of protein, ash, fat, lactose ratios and lightness (L*) were measured in samples with stevia. The addition of honey increased the b* values. The addition of cocoa increased pH and v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 27 publications
6
8
0
1
Order By: Relevance
“…Aerobic mesophilic bacterial count for the ice cream showed no significant difference between the treatments. These results are similar to those of Arslaner et al [24], who studied the effects of some sweeteners (sucrose, honey, and stevia) on the counts of standard plate in ice cream. They found that counts of standard plate were not statistically different between samples.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Aerobic mesophilic bacterial count for the ice cream showed no significant difference between the treatments. These results are similar to those of Arslaner et al [24], who studied the effects of some sweeteners (sucrose, honey, and stevia) on the counts of standard plate in ice cream. They found that counts of standard plate were not statistically different between samples.…”
Section: Discussionsupporting
confidence: 90%
“…The sugar patterns were observed according to Arslaner et al [24]. A five-gram sample was diluted with 20 mL of a water-methanol mix (75:25; v/v) and then centrifuged at 5000 g for 10 min at 5 • C. The supernatant was filtered using Whatman No.…”
Section: Sugar Profile Analysismentioning
confidence: 99%
“…The highest overrun value was observed in 1% stevia formulation, and the values decreased as stevia concentration increased. Overrun values found in this study were similar to those reported in other studies (Arslaner et al, 2019;Yazdi et al, 2020). Yazdi et al (2020) observed the reduction of overrun value of pistachio-peel-fortified ice cream from 28.01% to 21.63%, whereas Arslaner et al (2019) determined a reduction (from 24.55% to 22.53%) in stevia-fortified ice cream.…”
Section: Physicochemical Propertiessupporting
confidence: 90%
“…Overrun values found in this study were similar to those reported in other studies (Arslaner et al, 2019;Yazdi et al, 2020). Yazdi et al (2020) observed the reduction of overrun value of pistachio-peel-fortified ice cream from 28.01% to 21.63%, whereas Arslaner et al (2019) determined a reduction (from 24.55% to 22.53%) in stevia-fortified ice cream. However, overrun values in this study were lower than several literature findings such as 80%-100% (Ozdemir et al, 2007) and 65.12% (Pon et al, 2015).…”
Section: Physicochemical Propertiessupporting
confidence: 90%
See 1 more Smart Citation